Ethylene / CO interpolymer and its manufacturing process

JP7638334B2Active Publication Date: 2025-03-03DOW GLOBAL TECHNOLOGIES LLC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023118885
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-10-31
Filing Date
2023-07-21
Publication Date
2025-03-03
Estimated Expiration
2038-10-31

Smart Images

  • Figure 0007638334000020
    Figure 0007638334000020
  • Figure 0007638334000021
    Figure 0007638334000021
  • Figure 0007638334000022
    Figure 0007638334000022
Patent Text Reader

Abstract

To provide polymer compositions with good fiber-tear adhesion.SOLUTION: A composition comprises an ethylene / CO interpolymer formed from a high-pressure, free-radical polymerization, where the ethylene / CO interpolymer has the following properties: a) a CO content from "more than 0" wt.% to at most 10 wt.% CO (carbon monoxide), based on the weight of the interpolymer; and b) a melting point (Tm) in units of °C meeting the following relationship: Tm (°C)≤601.4×(density in g / cc)-452.5 (°C).SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Background technology]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application is a continuation of U.S. Provisional Patent Application No. 62 / 579,5 filed on October 31, 2017. This application claims priority from US Pat. No. 71, the entire contents of which are incorporated herein by reference. is.

[0002] Various polymers, including low density polyethylene (LDPE), are used to make paper and paperboard. Companies that extrusion coat fiberglass are finding that they have a high level of expertise in achieving good "fiber tear" adhesion. This fiber tearing adhesion is a constant problem between the polymer and the paper. is the amount of adhesion required to increase beyond the adhesion between the paper fibers. Adhesion is considered acceptable when the polymer is pulled from the paper substrate. Fiber tearing occurs when the bond is considered unacceptable because the paper When the polymer is pulled from the wire, no fibers come out (the fibers are not torn apart). In addition, in the extrusion lamination process used to manufacture multi-layer substrates, In any case, improved adhesion is desirable. The references in which Rimar is disclosed are as follows: International Publication No. WO 2014 / 1 05608, WO 2011 / 071843, WO 1991 / 18944 No. 2007 / 110127, No. 1997 / 45465, No. WO 2012 / 057975, WO 2012 / 084787; U.S. Pat. No. 23015; No. 6407191; No. 5178960; No. 3860538; Same No. 4714741; Same No. 6558809; Same No. 4962164; Same No. 36764 01; UK Patent No. 1448062; European Patent No. 0230143(B1); U.S. Patent Publication No. 2017 / 0114163; Publication No. 2017 / 0107315; Publication No. 200 No. 8 / 0242809, and Ethylene-Carbon Monoxide Extrudable Adhesive Copolymers for Polyv inylidene Chloride, June 1988 Tappi Journ al,pp.140-144;Scott et al. and Degradable Polymers,Principles and Applications,Cha pter 8:Ethylene-carbon monoxide copolyme rs, pp.156-168, Chapman and Hall (1995).

[0003] As is well known, extrusion coating lines using conventional polymers are produced at gradually increasing line speeds. If this is done, the resulting fiber tear bonds will be unacceptable. This adhesion occurs when the molten polymer exits the extrusion die and before it comes into contact with the paper (or The oxidation of the molten polymer occurs when the polymer is in the air gap. When the speed is increased, the molten polymer curtain is oxidized in a short time. It can be used in high speed extrusion coating lines. It has excellent melt strength and good adhesion to paper substrates, and can be used even at low melting temperatures. and / or can be used at high line speeds for paper substrates Thus, there exists a need for novel ethylene-based polymers. This resulted in the following invention: Summary of the Invention

[0004] Compositions containing ethylene / CO interpolymers formed by high pressure free radical polymerization. The ethylene / CO (carbon monoxide) interpolymer has the following properties: a) The CO content is "greater than 0" by weight based on the weight of the interpolymer. 10 percent CO (carbon monoxide) or less by weight. b) Melting point (T m ) (unit: °C) are related as follows: T m (℃) is 601.4 × (density, unit: g / cc) - 452.5 (℃) or less and satisfying the above. [Brief description of the drawings]

[0005] [Figure 1] 1 shows a reactor system used in the present invention. [Diagram 2] 1 shows a log scale plot of melt strength versus % CO level for an example of the present invention. [Diagram 3] 1 shows a linear scale plot of melt strength vs. CO level (%) for examples of the present invention. [Figure 4] 1 shows melting temperature versus density for examples of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0006] By using the ethylene / CO interpolymers described above, as well as further copolymers, This allows for increased melt strength and improved low temperature adhesion to substrates. It has been discovered that ethylene / CO interpolymers and copolymers can be prepared by mixing 2 to 100% by weight of the copolymers. When made with 3wt% CO, the melt strength was higher than when made with 1wt% or less CO. It has also been discovered that increasing the CO level of the sample The results showed that increasing the CO level improved adhesion at low temperatures compared to lowering the CO level. Obtained.

[0007] Compositions containing ethylene / CO interpolymers formed by high pressure free radical polymerization. The ethylene / CO interpolymer has the following properties: a) The CO content is "greater than 0" by weight based on the weight of the interpolymer. 10 to 10 weight percent CO (carbon monoxide) or less; b) Melting point (T m ) (unit: °C) are related as follows: T m (℃) is 601.4(℃ / (g / cc)) × (density, unit: g / cc) - and a temperature of 452.5°C or less. In the present invention, the ethylene / CO interpolymer is an ethylene / CO copolymer.

[0008] When the composition comprises a combination of two or more embodiments described herein, There is.

[0009] The ethylene / CO interpolymers, and further copolymers, are described herein. The present invention may include a combination of two or more embodiments.

[0010] As used herein, CO content refers to polymerized CO in the polymer. In the present invention, the CO content of the ethylene / CO interpolymer is based on the weight of the interpolymer. Standard: 0.1wt% to less than 10wt%, or 0.2 to less than 10wt%, or 0.5 In a further embodiment, the ethylene / CO interpolyether is from 0.1 wt% to less than 10 wt%. The mer is an ethylene / CO copolymer.

[0011] In one embodiment, the CO content of the ethylene / CO interpolymer is 1.0wt%~9.0wt%, or 1.0wt%~9.0wt% based on the weight of the polymer t% or 1.2~8.0wt%, or 1.4wt%~7.0wt%, or 1.6w % to 6.0 wt%, or 1.8 wt% to 5.0 wt%. Thus, the ethylene / CO interpolymer is an ethylene / CO copolymer.

[0012] In one embodiment, the CO content of the ethylene / CO interpolymer is 1.2wt% or more, or 1.4wt% or more, or 1.6wt% or more, based on the weight of the polymer t% or more, or 1.8wt% or more, or 2.0wt% or more, or 2.2wt% or more In a further embodiment, the ethylene / CO interpolymer is 2.4 wt.% or more. In one embodiment, the polymer is an ethylene / CO copolymer. The CO content of the terpolymer is 4.0 wt.% or less, based on the weight of the interpolymer; or 3.8 wt% or less, or 3.6 wt% or less, or 3.4 wt% or less, or 3 In a further embodiment, the ethylene / CO interpolymer has It is an ethylene / CO copolymer.

[0013] In one embodiment, the ethylene / CO interpolymer has the following relationship: MS(cN) ≧2.0×(wt%CO)+2.0. In a further embodiment, the ethylene / CO The interpolymer is an ethylene / CO copolymer.

[0014] In one embodiment, the melt index (I ) is 0.1 to 100g / 10min, or 0.5 to 50g / 10min, or 1.0 to 30 g / 10 min. In addition, the melt index (I 2) 0.1-6g / 10min, or 0.3-3g / 10min, or 0.3-0.7g In a further embodiment, the ethylene / CO interpolymer may be It is a styrene / CO copolymer.

[0015] In one embodiment, the melt index (I ) is 1.5g / 10min or more, or 2.0g / 10min or more, or 2.5g / 10min or more or above, or 3.0 g / 10 min or greater, or 3.5 g / 10 min or greater. In the above, the ethylene / CO interpolymer is an ethylene / CO copolymer. In an embodiment, the melt index (I2) of the ethylene / CO interpolymer is 2 0g / 10min or less, or 15g / 10min or less, or 10g / 10min or less, or 8. 0g / 10min or less, or 7.0g / 10min or less, or 6.0g / 10min or less. In a further embodiment, the ethylene / CO interpolymer is an ethylene / CO copolymer. -It is.

[0016] In one embodiment, the T of the ethylene / CO interpolymer m (℃) is 601.4 (℃ / (g / cc)) × (density, unit: g / cc) - 460.0 (℃) or more. In some embodiments, the ethylene / CO interpolymer is an ethylene / CO copolymer. be.

[0017] In one embodiment, the melting temperature (T m ) is 10 2°C or higher, or 103°C or higher, or 104°C or higher, or 105°C or higher, or 10 6°C or higher (calculated by DSC (peak temperature)). In one embodiment, the ethylene / CO interpolymer is an ethylene / CO copolymer. Melting temperature (T m ) is below 114℃ or 113℃ or less than 112℃, or less than 111℃, or less than 110℃, or less than 109℃ In a further embodiment, the ethylene / The CO interpolymer is an ethylene / CO copolymer.

[0018] In one embodiment, the melting temperature (T m ) is 102℃~114℃ ℃, or 103℃~113℃, or 104℃~112℃, or 105℃~111℃ , or 106°C to 110°C (calculated by DSC (peak temperature)). In an embodiment, the ethylene / CO interpolymer is an ethylene / CO copolymer.

[0019] In one embodiment, the crystallization temperature (T c ) is 9 1℃ or higher, or 92℃ or higher, or 93℃ or higher, or 94℃ or higher (DSC (peak temperature In a further embodiment, the ethylene / CO interpolymer has a molecular weight of 1.01 to 1.01 mm. In one embodiment, the ethylene / CO interpolymer is an ethylene / CO copolymer. The crystallization temperature of the mer (T c ) is 99°C or less, or 98°C or less, or 97°C or less, In a further embodiment, the temperature is 96° C. or less (calculated by DSC (peak temperature)). The ethylene / CO interpolymer is an ethylene / CO copolymer.

[0020] In one embodiment, the ethylene / CO interpolymer has a percent crystallinity of 45 or greater. or 46 or more, or 47 or more, or 48 or more, or 49 or more (DSC(P In a further embodiment, the ethylene / CO interpolymer In one embodiment, the ethylene / CO interpolymer is an ethylene / CO copolymer. The percent crystallinity of the polymer is 55 or less, or 54 or less, or 53 or less, or 52 or less. or less, or 51 or less (calculated by DSC (peak temperature)). In this case, the ethylene / CO interpolymer is an ethylene / CO copolymer.

[0021] In one embodiment, the density of the ethylene / CO interpolymer is 0.940 g / c c or more, or 0.945g / cc or more, or 0.950g / cc or more, or 0.9 55g / cc or more (1cc=1cm 3 In a further embodiment, ethylene / C The O interpolymer is an ethylene / CO copolymer. In one embodiment, the ethylene The density of the PO / CO interpolymer is 0.990 g / cc or less, or 0.985 g / cc or less. c or less, or 0.980g / cc or less, or 0.975g / cc or less, or 0.9 In a further embodiment, the ethylene / CO interpolymer has a modulus of elasticity of about 70 g / cc or less. , an ethylene / CO copolymer.

[0022] In one embodiment, the density of the ethylene / CO interpolymer is 0.910 g / c c or more, or 0.912g / cc or more, or 0.915g / cc or more, or 0.9 18g / cc or more, or 0.920g / cc or more, or 0.922g / cc or more, or or 0.925g / cc or more, or 0.928g / cc or more, or 0.930g / cc or more c or more, or 0.932g / cc or more, or 0.935g / cc or more (1cc=1c m 3 In a further embodiment, the ethylene / CO interpolymer is ethylene In one embodiment, the ethylene / CO interpolymer has a density of is 0.950g / cc or less, or 0.948g / cc or less, or 0.945g / cc c or less, or 0.942 g / cc or less, or 0.941 g / cc or less. In an embodiment, the ethylene / CO interpolymer is an ethylene / CO copolymer. do.

[0023] In one embodiment, the density of the ethylene / CO interpolymer is from 0.910 to 0. 950g / cc(1cc=1cm 3 ), or 0.920~0.950g / cc, or 0.925~0.950g / cc, or 0.930~0.945g / cc, or 0. In a further embodiment, the ethylene / CO interpolymer is 935 to 0.942 g / cc. The polymer is an ethylene / CO copolymer.

[0024] In one embodiment, the molecular weight distribution of the ethylene / CO interpolymer (cc-GPC Mw / Mn) is 8.0 or more, or 8.5 or more, or 9.0 or more, or 9.5 or more In a further embodiment, the ethylene / CO interpoly In one embodiment, the ethylene / CO interpolymer is an ethylene / CO copolymer. - The molecular weight distribution (cc-GPC Mw / Mn) of the polymer is 15.0 or less, or 14. 5 or less, or 14.0 or less, or 13.5 or less, or 13.0 or less, or 12. 5 or less, or 12.0 or less. In a further embodiment, the ethylene / CO interfacial ratio is The polymer is an ethylene / CO copolymer.

[0025] In one embodiment, the molecular weight distribution of the ethylene / CO interpolymer (cc-GPC Mw / Mn) is 8.0-14.0, further 9.0-13.0, and further 10.0-12. 0 (calculated by conventional GPC). In a further embodiment, the ethylene / CO interphase The polymer is an ethylene / CO copolymer.

[0026] In an alternative embodiment, the molecular weight distribution (cc-G PC Mw / Mn) is 3-12, or 4-11, or 4.5-11.

[0027] In one embodiment, the number average molecular weight (cc-GP C Mn) is 10,000 g / mol or more, or 11,000 g / mol or more, or is 12,000 g / mol or more, or 13,000 g / mol or more. In the embodiment, the ethylene / CO interpolymer is an ethylene / CO copolymer. In one embodiment, the number average molecular weight (cc-GPC) of the ethylene / CO interpolymer is Mn) is 20,000 g / mol or less, or 19,000 g / mol or less, or 1 8,000g / mol or less, or 17,000g / mol or less, or 16,000g In a further embodiment, the ethylene glycol ether is 0.1 to 1.0 g / mol or less, or 15,000 g / mol or less. The ethylene / CO interpolymer is an ethylene / CO copolymer.

[0028] In one embodiment, the ethylene-based polymer has a number average molecular weight (Mn) of 10,000 g / mol~25,000g / mol, and even 10,000g / mol~20,000g / mol, and even 11,000g / mol to 19,000g / mol, and even 11,00 0g / mol~16,000g / mol, and even 12,000g / mol~15,000 g / mol (calculated by conventional GPC). In a further embodiment, the ethylene / C The O interpolymer is an ethylene / CO copolymer.

[0029] In one embodiment, the weight average molecular weight (cc-G PC Mw) is 100,000g / mol or more, 130,000g / mol or more, is 135,000 g / mol or more, or 140,000 g / mol or more, or 145 In one embodiment, the ethylene / CO interpolymer has a molecular weight of 1,000 g / mol or more. The weight average molecular weight (cc-GPC Mw) of the polymer is 200,000 g / mol or less, or 1 95,000g / mol or less, or 190,000g / mol or less, or 185,0 00 g / mol or less, or 180,000 g / mol or less. In this case, the ethylene / CO interpolymer is an ethylene / CO copolymer.

[0030] In one embodiment, the weight average molecular weight (Mw) of the ethylene / CO interpolymer is , 135,000g / mol to 190,000g / mol, and even 140,000g / m ol~185,000g / mol, and even 145,000g / mol~180,000g / mol (calculated by conventional GPC). In a further embodiment, the ethylene / CO The interpolymer is an ethylene / CO copolymer.

[0031] In an alternative embodiment, the weight average molecular weight (cc) of the ethylene / CO interpolymer -GPC Mw) is 60,000-150,000g / mol, or 65,000- Can be 150,000 g / mol, or 70,000 to 145,000 g / mol .

[0032] In one embodiment, the loss tangent (0.1 rad / sec, 190℃) is 1.50 or more, 2.00 or more, 3.00 or more, or 3.10 or more, Or 3.20 or greater, or 3.30 or greater, or 3.40 or greater. In the above, the ethylene / CO interpolymer is an ethylene / CO copolymer. In an embodiment, the loss tangent (0.1 rad / sec, 19 0°C) is 6.40 g / mol or less, or 6.20 g / mol or less, or 6.00 g / mol or less, or 5.80 g / mol or less, or 5.60 g / mol or less. In a further embodiment, the ethylene / CO interpolymer is an ethylene / CO copolymer. -It is.

[0033] In one embodiment, the viscosity of the ethylene / CO interpolymer (0.1 rad / sec, 190℃) is 1800 Pa·s or more, 2,000 Pa·s or more, or 2,200 Pa·s or more s or more, or 2,400 Pa·s or more, or 2,600 Pa·s or more, or 2, In a further embodiment, the ethylene / CO interpolymer has a viscosity of 800 Pa·s or more. In one embodiment, the ethylene / CO interpolymer is The viscosity of the polymer (0.1rad / sec, 190℃) is 5,000Pa·s or less, or 4, 800 Pa s or less, or 4,600 Pa s or less, or 4,400 Pa s or less, Or 4,200 Pa·s or less, or 4,000 Pa·s or less, or 25,000 Pa·s In a further embodiment, the viscosity of the ethylene / CO interpolymer ( 0.1rad / sec, 190℃) is 1800~30,000Pa·s, or 2000~ In a further embodiment, the ethylene / CO interpolymer has a viscosity of 25,000 Pa·s. is an ethylene / CO copolymer.

[0034] In one embodiment, the viscosity of the ethylene / CO interpolymer (100 rad / sec, 190℃) is 200 Pa·s or more, 220 Pa·s or more, 240 Pa·s or more, 260 Pa·s or more, or 270Pa·s or more, or 280Pa·s or more, or 290P a·s or more, or 300 Pa·s or more. The O interpolymer is an ethylene / CO copolymer. In one embodiment, the ethylene The viscosity of the ethylene / CO interpolymer (100 rad / sec, 190°C) is 370 Pa·s or more. or below 360 Pa·s, or below 350 Pa·s, or below 340 Pa·s , or 330 Pa·s or less, or 320 Pa·s or less, or 800 Pa·s or less In a further embodiment, the viscosity (100 rad) of the ethylene / CO interpolymer is / sec, 190°C) is 200 to 1,000 Pa·s, or 220 to 800 Pa·s. In a further embodiment, the ethylene / CO interpolymer is an ethylene / CO copolymer. It's Rimmer.

[0035] In one embodiment, the viscosity ratio of the ethylene / CO interpolymer (V0.1 / V10 0, 190℃) is 7.0 or more, or 7.5 or more, or 8.0 or more, or 8.5 or more or above 9.0, or above 9.5, or above 15, or above 20, or 3 In a further embodiment, the ethylene / CO interpolymer is In one embodiment, the viscosity of the ethylene / CO interpolymer is The ratio (V0.1 / V100, 190℃) is 15.5 or less, or 15.0 or less, or 1 4.5 or less, or 14.0 or less, or 13.5 or less, or 13.0 or less, or 1 In a further embodiment, the ethylene / CO ratio is 2.0 or less, or 11.0 or less. The terpolymer is an ethylene / CO copolymer.

[0036] In one embodiment, the ethylene / CO interpolymer has a gpcBR of 2.45 or greater. or above, or 2.50 or above, or 2.55 or above, or 2.60 or above, or 2.65 or above In a further embodiment, the ethylene / CO interpoly In one embodiment, the ethylene / CO interpolymer is an ethylene / CO copolymer. - The gpcBR of the polymer is 3.20 or less, or 3.15 or less, or 3.10 or less; Or 3.05 or less, or 3.00 or less, or 2.95 or less. In the above, the ethylene / CO interpolymer is an ethylene / CO copolymer. In an embodiment, the gpcBR of the ethylene-based polymer is 2.50 to 3.20, or even 2. In a further embodiment, the ethylene The ethylene / CO interpolymer is an ethylene / CO copolymer. The gpcBR of ethylene-based polymers is 1.00-3.20, or 1.10-3.10, or or 1.10 to 3.00.

[0037] In one embodiment, the amyl (C5) group level of the ethylene / CO interpolymer is , 0.50 amyl groups or more per 1000 carbon atoms, or 0 per 1000 carbon atoms .75 amyl groups or more, or 1.00 amyl groups or more per 1000 carbon atoms, or More than 1.10 amyl groups per 1000 atoms or 1.2 per 1000 carbon atoms 0 or more amyl groups ( 13 C NMR). In one embodiment, the ethylene / CO interpolymer is an ethylene / CO copolymer. The amyl (C5) group level of ethylene / CO interpolymers is Not more than 5.00 amyl groups per 1,000 carbon atoms, or not more than 4.00 amyl groups per 1,000 carbon atoms, or Not more than 3.00 amyl groups per 1000 carbon atoms, or 2.00 amyl groups per 1000 carbon atoms .00 amyl group or less ( 13 In a further embodiment, The ethylene / CO interpolymer is an ethylene / CO copolymer.

[0038] In one embodiment, the vinyl group level of the ethylene / CO interpolymer is 0.030 vinyl groups per 1000 molecules or 0.03 per 1000 carbon atoms 5 vinyl groups or more, or 0.050 vinyl groups or more per 1000 carbon atoms, or More than 0.055 vinyl groups per 1000 atoms, or 0.0 per 1000 carbon atoms 60 vinyl groups or more, or 0.065 vinyl groups or more per 1000 carbon atoms, or More than 0.070 vinyl groups per 1000 atoms ( 1 1 H NMR). In one embodiment, the ethylene / CO interpolymer is an ethylene / CO copolymer. In one embodiment, the vinyl group level of the ethylene / CO interpolymer is Not more than 0.250 vinyl groups per 1000 atoms, or 0. Not more than 200 vinyl groups, or not more than 0.110 vinyl groups per 1000 carbon atoms, or Not more than 0.105 vinyl groups per 1000 carbon atoms, or 0 Not more than .100 vinyl groups or not more than .090 vinyl groups per 1000 carbon atoms, is 0.095 vinyl groups or less per 1000 carbon atoms ( 1 1 H NMR) In a further embodiment, the ethylene / CO interpolymer is an ethylene / CO copolymer. It's Ma.

[0039] In one embodiment, the total unsaturation level of the ethylene / CO interpolymer is More than 0.15 unsaturated per 1000 carbon atoms, more than 0.20 unsaturated per 1000 carbon atoms Saturated or unsaturated at least 0.22 per 1000 carbon atoms, or 0.24 or more unsaturations per atom, or 0.26 or more unsaturations per 1000 carbon atoms or 0.28 or more unsaturations per 1000 carbon atoms ( 1 Calculated by H NMR In a further embodiment, the ethylene / CO interpolymer is In one embodiment, the total unsaturation level of the ethylene / CO interpolymer is The olefins have less than 0.60 unsaturations per 1000 carbon atoms, or Not more than 0.55 unsaturations per 1000 carbon atoms, or not more than 0.44 unsaturations per 1000 carbon atoms, has 0.42 or less unsaturations per 1000 carbon atoms, or 0 Not more than 0.40 unsaturations or 0.38 unsaturations or Unsaturation of 0.36 or less per 1000 atoms ( 1 1 H NMR). In some embodiments, the ethylene / CO interpolymer is an ethylene / CO copolymer. be.

[0040] In one embodiment, the ethylene / CO interpolymer is % or more, or 85% or more, by weight of polymerized ethylene. In the embodiment, the ethylene / CO interpolymer is an ethylene / CO copolymer. In one embodiment, the ethylene / CO interpolymer is, based on the weight of the interpolymer, % or more by weight of polymerized ethylene, based on the weight of the polymer. In the above formula, the ethylene / CO interpolymer is an ethylene / CO copolymer.

[0041] In one embodiment, the ethylene / CO interpolymer is a low molecular weight copolymer comprising a CO comonomer. In a further embodiment, the ethylene / CO interpolymer is a low density polyethylene (LDPE). The polymer is an ethylene / CO copolymer.

[0042] In one embodiment, the ethylene / CO interpolymer is a copolymer of ethylene and In a further embodiment, the copolymer comprises CO as the only monomer type. Ethylene / CO copolymers contain a majority of polymerized ethylene based on the weight of the copolymer. In a further embodiment, the ethylene / CO copolymer comprises, based on the weight of the copolymer, Contains 90 wt% or more, or 95 wt% or more, or 98 wt% or more of polymerized ethylene. nothing.

[0043] In one embodiment, the ethylene / CO interpolymer is, by weight of the composition, 10wt% or more, or 20wt% or more, or 30wt% or more, or 40wt% or more, or 50wt% or more, or 60wt% or more, or 70wt% or more, or 8 0wt% or more, or 90wt% or more, or 95wt% or more, or 98wt% or more, In a further embodiment, the ethylene / CO interpolymer is present in an amount of 99 wt % or more. The polymer is an ethylene / CO copolymer.

[0044] In one embodiment, the ethylene / CO interpolymer is, by weight of the composition, In further embodiments, the cellulose is present in an amount of 10 to 50 wt %, or 20 to 40 wt %. In one embodiment, the ethylene / CO interpolymer is an ethylene / CO copolymer. In this embodiment, the ethylene / CO interpolymer is 60 to 90% by weight of the composition. In a further embodiment, ethylene is present in an amount of 0 wt%, or 65-85 wt%. In one embodiment, the ethylene / CO interpolymer is an ethylene / CO copolymer. The ethylene / CO interpolymer is present in an amount of from 1.0 to 10 wt. %, based on the weight of the composition; Or in an amount of 1.5 to 5.0 wt %. In a further embodiment, ethylene / C The O interpolymer is an ethylene / CO copolymer.

[0045] In one embodiment, the composition further comprises a second ethylene-based polymer. In an embodiment, the second ethylene-based polymer is a LDPE, an ethylene / α-olefin ethylene copolymer. terpolymers, or combinations thereof.

[0046] In one embodiment, the composition further comprises another ethylene-based polymer. Polyolefin polymers are characterized by a number of properties such as density, melt index, comonomer, and comonomer content. At least one property is different from the ethylene / CO interpolymers and further copolymers. Other suitable ethylene-based polymers include, but are not limited to, DOWLEX poly(ethylene glycol). Ethylene resin, TUFLIN linear low density polyethylene (LLDPE) resin, ELITE and and / or ELITE AT reinforced polyethylene resin (both from The Dow Chemical Company) available from ), high density polyethylene (d ≥ 0.955g / cc), medium density polyethylene ( Density 0.935~0.955g / cc), EXCEED polymer and ENABLE polymer - (both manufactured by ExxonMobil), LDPE, and EVA (Ethylene Vinyl Vinyl Acetate) ) are mentioned.

[0047] In one embodiment, the composition further comprises a propylene-based polymer. Polypropylene homopolymer, propylene / α-olefin copolymer, propylene / ethylene interpolymers and copolymers; Polymers are included.

[0048] In one embodiment, the composition further comprises a heterogeneously branched ethylene / α-olefin. Interpolymers, preferably heterogeneously branched ethylene / α-olefin copolymers In one embodiment, the heterogeneously branched ethylene / α-olefin interpolymer For preferably heterogeneously branched ethylene / α-olefin copolymers, the density is 0.89 to 0.94 g / cc, or even 0.90 to 0.93 g / cc. In some embodiments, the composition comprises from 1 to 99 weight percent, based on the weight of the composition, The copolymer comprises 15 to 85 weight percent of the ethylene / CO interpolymer. In the above formula, the ethylene / CO interpolymer is an ethylene / CO copolymer.

[0049] In one embodiment, the sulfur content of the composition is 5 parts by weight of the composition. pm or even less than 2 ppm or even less than 1 ppm or even less than 0.5 ppm. In one embodiment, the composition is sulfur-free.

[0050] In one embodiment, the composition comprises 1.5 to 80 wt% based on the weight of the composition. ethylene / CO interpolymers, and further ethylene / CO copolymers. In some embodiments, the composition further comprises LLDPE.

[0051] In one embodiment, the composition comprises 1.5 to 20 wt. % based on the weight of the composition. ethylene / CO interpolymers, and further ethylene / CO copolymers. In some embodiments, the composition further comprises LLDPE.

[0052] In one embodiment, the composition comprises, based on the weight of the composition, 20 to 80 wt. % or 30-80 wt%, or 40-80 wt%, or 50-80 wt% ethylene Further embodiments include ethylene / CO interpolymers, and further ethylene / CO copolymers. wherein the composition further comprises LLDPE.

[0053] The compositions of the present invention include combinations of two or more of the embodiments described herein. The ethylene / CO interpolymers of the present invention may be The ethylene / CO copolymer of the present invention may comprise a combination of two or more embodiments. may include a combination of two or more embodiments described herein.

[0054] Also provided herein is a composition comprising at least one embodiment of the composition. Also provided is an article comprising at least one of the components. The article is a coated substrate or film.

[0055] In one embodiment, the article is made by extrusion coating or extrusion lamination. In one embodiment, the article is a coated substrate. In a further embodiment, the substrate is a paper product. In one embodiment, the article comprises: In a further embodiment, the substrate is a paper product. In some embodiments, the article is manufactured by extrusion coating or extrusion lamination. The article of the invention may include a combination of two or more of the embodiments described herein. There are cases.

[0056] The present invention also provides a composition formed from one or more of the embodiments described herein. The coating of the present invention comprises two or more of the compositions described herein. The present invention may include a combination of the above embodiments.

[0057] Also provided herein are processes for forming the compositions of one or more of the embodiments described herein. The process also provides a process for producing ethyl acetate using a high pressure free radical polymerization process. polymerizing ethylene and CO to form an ethylene / CO interpolymer; and The reactor configuration in which the polymerization occurs is a small reactor with two or more reaction zones. At least one autoclave reactor and at least one reactor with two or more reaction zones. and a tubular reactor, and in the autoclave reactor, polymerization is carried out by Rm auto At least one "medium temperature free radical initiator" labeled FRl auto Polymerization in the presence of at least one "low temperature free radical initiator" labeled FRm occurs in each reaction zone in the autoclave reactor. auto vs. FRL aut o Weight ratio auto ) is 0.04 to 1.00, and In the tubular reactor, the polymerization is carried out by tube At least one marked "High temperature free radical initiator", and FRm tube At least one "medium" marked Polymerization occurs in the presence of a "warm free radical initiator" and each of the FRh in the reaction zone tube vs. FRm tube Weight ratio tube ) is 0. In a further embodiment, the ethylene / CO interpolymer has It is an ethylene / CO copolymer.

[0058] In one embodiment, FRm is added to each reaction zone in the autoclave reactor. auto vs. FRL auto Weight ratio auto ) is 0.05 or more, or 0.06 or less or above, or 0.07 or above, or 0.08 or above, or 0.09 or above, or 0.10 or above or greater than 0.11, or greater than 0.12. In one embodiment, the ethylene / CO interpolymer is an ethylene / CO copolymer. FRm in each reaction zone in the autoclave reactor auto vs. FRL auto Weight ratio of (ratio auto ) is 0.90 or less, or 0.80 or less, or 0.70 or less, Or 0.60 or less, or 0.50 or less, or 0.40. In this case, the ethylene / CO interpolymer is an ethylene / CO copolymer.

[0059] In one embodiment, FRh is added to each reaction zone in the tubular reactor. tube Against F Rm tube Weight ratio tube ) is 0.07 or more, or 0.08 or more, Or 0.09 or more, or 0.10 or more, or 0.11 or more. In the above, the ethylene / CO interpolymer is an ethylene / CO copolymer. In an embodiment, FRh is added to each reaction zone in the tubular reactor. tube vs. FRm tu be Weight ratio tube ) is less than or equal to 0.45, or less than or equal to 0.40, or 0 0.35 or less, or 0.30 or less, or 0.25 or less, or 0.20 or less. In one embodiment, the ethylene / CO interpolymer is an ethylene / CO copolymer. It is.

[0060] In one embodiment, in an autoclave reactor, "ethyl acetate added to the reaction zone" The weight ratio of the amount of benzene added to the amount of CO added to the same reaction zone is greater than or equal to 30 or less than 3. 5 or more, or 40 or more, or 45 or more, or 50 or more, or 55 or more, or 6 0 or greater, or 65 or greater. In a further embodiment, the ethylene / CO interpoly In one embodiment, the copolymer added to the reaction zone is an ethylene / CO copolymer. The weight ratio of the amount of ethylene added to the reaction zone to the amount of CO added to the same reaction zone is 400 or less. , or 395 or less, or 390 or less, or 385 or less, or 380 or less, or In a further embodiment, the ethylene / CO interpolymer has a modulus of 375 or less. It is a ethylene / CO copolymer.

[0061] In one embodiment, in an autoclave reactor, "ethyl acetate added to the reaction zone" The weight ratio of the amount of benzene added to the amount of CO added to the same reaction zone is 95 or greater, or 1. 00 or more, or 105 or more, or 110 or more. The ethylene / CO interpolymer is an ethylene / CO copolymer. The amount of ethylene added to a reaction zone versus the amount of CO added to the same reaction zone. The weight ratio of is 205 or less, or 200 or less, or 195 or less, or 190 or less, or or 185 or less, or 180 or less. The terpolymer is an ethylene / CO copolymer.

[0062] In one embodiment, in an autoclave reactor, "ethyl acetate added to the reaction zone" The weight ratio of the amount of benzene to the amount of CO added to the same reaction zone is 388 to 39. In a further embodiment, the ethylene / CO interpolymer is an ethylene / CO copolymer. It's Ma.

[0063] In one embodiment, the polymerization temperature of each reaction zone of the autoclave reactor is independently 190℃~270℃, or 200℃~260℃, or 210℃~250℃, or 220° C. to 240° C. In a further embodiment, the ethylene / CO interpolymer is an ethylene / CO copolymer.

[0064] In one embodiment, the polymerization temperature of each reaction zone of the autoclave reactor is independently The temperature is preferably less than 250°C, or less than 245°C, or less than 240°C, or less than 235°C. In one embodiment, the ethylene / CO interpolymer is an ethylene / CO copolymer. It is.

[0065] In one embodiment, the polymerization temperature in each reaction zone in the tubular reactor is independently 260℃~300℃, or 265℃~295℃, or 270℃~290℃, or 270° C. to 285° C. In a further embodiment, the ethylene / CO interpolymer is an ethylene / CO copolymer. The process of the present invention includes a combination of two or more of the embodiments described herein. This may be the case.

[0066] process To prepare the ethylene / CO interpolymer or copolymer, the methods described herein include As described above, high pressure free radical initiated polymerization is used. There are two types of free radical initiated polymerization process. The first type involves one or more A stirred autoclave vessel having the above reaction zone is used. An actor typically has several injection points for initiator and / or monomer feedstock. In the second type, a jacketed tube with one or more reaction zones is used. A tube is used as the reactor. The length of the suitable reactor is not limited. However, it can be 100 to 3000 meters (m), or 1000 to 2000 m. The initiation of the reaction zone in any type of reactor usually involves the introduction of some kind of initiator, e.g. For example, ethylene, chain transfer agents (or telomers), comonomers, and any combination thereof. It is commonly defined as a side injection with a High pressure processes are carried out in autoclaves or tubular reactors, where one or more reaction vessels are A reactor with a reaction zone may be used, or an autoclave and a tubular rear A combination of reactors, each containing one or more reaction zones, may be used.

[0067] The molecular weight can be controlled by using a chain transfer agent (CTA). In one embodiment, one or more chain transfer agents (CTAs) are added to the polymerization process of the present invention. Representative CTAs that may be used include, but are not limited to, propylene, isobutane. , n-butane, 1-butene, methyl ethyl ketone, acetone, and propionaldehyde In one embodiment, the amount of CTA used in the process is It is 0.03 to 10 weight percent of the total mixture.

[0068] The ethylene used in the production of ethylene / CO interpolymers is purified ethylene. This purified ethylene may be used to remove polar components from the loop recycle stream. This can be achieved by removal or by using a reaction system configuration. As a result, only fresh ethylene is used to produce the polymers of the present invention. However, sometimes only purified ethylene is needed to produce ethylene-based polymers. In such cases, ethylene obtained from the recycle loop may be used.

[0069] Additives The compositions of the present invention may include one or more additives, including but not limited to: However, stabilizers, plasticizers, antistatic agents, pigments, dyes, nucleating agents, fillers, slip agents, etc. agents, flame retardants, processing aids, smoke suppressants, viscosity modifiers, and antiblocking agents. The polymer composition may, for example, comprise less than 10% ( The composition may contain one or more additives (by combined weight).

[0070] In one embodiment, the polymers of the present invention may be provided with one or more stabilizers, such as IRGAN. OX1010, IRGANOX1076, and IRGAFOS168 (Chiba Specialty The polymer is treated with an antioxidant such as ethylene glycol terephthalate (Eds. Chemicals, Glattbrugg, Switzerland). are typically treated with one or more stabilizers prior to extrusion or other melt processing. Processing aids such as plasticizers include, but are not limited to, di-phthalate. Phthalates such as octyl and diisobutyl phthalate, lanolin and paraffin Natural oils, naphthenic and aromatic oils obtained by petroleum refining, rosin or oil-derived oils An exemplary class of oils useful as processing aids includes the liquid resins of KAYD OL Oil (Chemtura Corporation; Middlebury, Connecticut), and SHE such as LLFLEX371 naphthenic oil (Shell Lubricants; Houston, TX). White mineral oils include TUFFLO Oil (Lyondell Lubricants, Texas) Houston) is another suitable oil.

[0071] Blends and mixtures of the polymers of the present invention with other polymers may also be practiced. Suitable polymers for blending with the polymer of the present invention include natural and synthetic polymers. Exemplary polymers for blending include propylene-based polymers (e.g., impact-resistant Impact-modified polypropylene, isotactic polypropylene, atactic polypropylene ethylene and random ethylene / propylene copolymers; various types of ethylene-based polymers; For example, high pressure, free radical LDPE, LLDP prepared with Ziegler-Natta catalyst E: PE (polyethylene) prepared with single-site catalyst, e.g., multi-reactor PE ( "In-reactor" blending of Ziegler-Natta PE and single-site catalyst PE, See, e.g., U.S. Pat. No. 6,545,088 (Kolthammer et al.); No. 6,538,070 (Cardwell, et al.); No. 6,566,446 No. (Parikh, et al.); No. 5,844,045 (Kolthammer) et al.); No. 5,869,575 (Kolthammer et al.) and 6,448,341 (Kolthammer et al.). (Products that are used));EVA;Ethylene / vinyl alcohol copolymer;Polystyrene;Impact modified Modified polystyrene; ABS; styrene / butadiene block copolymers and their hydrogenated derivatives. Polyurethanes (SBS and SEBS); and thermoplastic polyurethanes. Homopolymers such as lastomers and elastomers, ethylene and propylene based copolymers - (For example, the product name VERSIFY Plastomers & Elastomers ( Chemical Company) and VISTAMAXX (ExxonMobil Chemical Company) ) are also useful as components of blends containing the polymers of the present invention. It could be.

[0072] Purpose Ethylene / CO interpolymer-containing compositions are useful in a variety of extrusion coating applications (e.g., Gar pouches, paper boards, hot and cold beverage cups, gable top cartons, non-woven fabrics, woven fabrics substrates, toothpaste tubes, stand-up pouches, or other substrates) However, conventional LDPE or LLDPE (or blends of either) polymers are The polymers of the present invention have also been found to be disadvantageous due to their poor adhesion to sterile drills. Bin boxes, snack packaging, ream wraps, stand up pouches, toothpaste Improved adhesion in multi-layer structures such as tubes, cheese packages, and laminated films In various extrusion laminations, or other LDPE or LLDPE (or any blend) is disadvantaged due to poor adhesion. It can be used in extrusion lamination, which has been shown to be

[0073] The compositions of the present invention can be used in a variety of conventional thermoplastic processing processes to produce monolayer These make it possible to manufacture useful articles including polymers and multi-layer films. Means for producing useful articles include blown film processes (e.g., air blown film). cold blown film process; cast film or cast sheet process (e.g., by using chill rollers to quench the extruded molten polymer); or film or sheet extrusion (e.g., using a water bath). These articles include not only films but also molded articles (e.g., blow molded, injection molded, or rotationally molded articles; coatings; fibers; and woven or nonwoven fabrics). .

[0074] The types of films in which compositions containing ethylene / CO interpolymers are used are: These applications are many and varied, including but not limited to extrusion coating, food packaging, , Consumer, Industrial, Agriculture (Application or Film), Lamination Film, Fresh cut produce film, meat film, cheese film, candy film, Transparency shrink film, collated shrink film, stretch film, grass packing film, greenhouse film Films, fumigation films, interior lining films, stretchable hoods, heavy-duty transport bags, pet food Examples of applications include bags, sandwich bags, sealants, and outer covers for diapers.

[0075] The ethylene / CO interpolymer-containing compositions are useful for coating wire and cable. Sheet extrusion for injection molding, blow molding processes, and vacuum forming operations. The polymers of the present invention can also be used in applications such as forming molded articles, including using rotational molding processes. Other suitable applications for the polymer include elastic films and fibers, and soft objects such as appliance handles. Soft Touch Goods;Gaskets & Profiles;Auto Interior Parts & Profiles;Foam Products (both open and closed cell); high density polyethylene and other olefin polymers impact modifiers for other thermoplastic polymers such as; cap linings; and flooring materials Examples include:

[0076] definition As used herein, the phrase "high pressure free radical polymerization process" refers to at least one Free radical initiated polymerization carried out at high pressures of at least 1000 bar (100 MPa) Point.

[0077] As used herein, the term "polymer" refers to different types of polymers of the same type. Polymers also refer to polymeric compounds prepared by polymerizing monomers. The generic term polymer includes the term homopolymer (prepared from only one type of monomer). refers to polymers, with the understanding that trace amounts of impurities may be incorporated into the polymer structure. and interpolymer, as defined below. Trace impurities (e.g., catalyst residues) may be incorporated into the polymer and / or may be In some cases, the system may be incorporated into the

[0078] As used herein, the term "interpolymer" means a polymer having at least two Refers to polymers prepared by polymerizing different types of monomers. A generic term for polymers is copolymers (polymers prepared from two different types of monomers). (used to refer to monomers) and those prepared from three or more different types of monomers. and polymers having the same structure.

[0079] As used herein, the term "ethylene-based polymer" means a polymer having a molecular weight of 1,000 to 1,000. 50% or a majority of polymerized ethylene monomer (by weight, based on total weight) Both terms refer to polymers that may contain one comonomer.

[0080] As used herein, the term "ethylene / α-olefin interpolymer" refers to The term refers to copolymers containing 50 wt. % or a majority of polymerized ethylene (based on the weight of the interpolymer). The present invention refers to an interpolymer comprising an olefin monomer and at least one α-olefin. As used herein, the term "ethylene / α-olefin copolymer" means a copolymer of 50% or a majority of polymerized ethylene monomer and α-olefin monomer (based on the weight of the polymer) This refers to a copolymer that contains (as the only two monomer types) fin and fins.

[0081] As used herein, the term "ethylene / CO interpolymer" means ( 50 wt. % or a majority of polymerized ethylene monomer (based on the weight of the interpolymer) and carbon monoxide (CO). The term "ethylene / CO polymer" means a copolymer having a molecular weight of 50 wt. % or a majority of polymerized ethylene monomer and carbon monoxide (CO) (the only two monomers This refers to copolymers containing tertiary amines (as one type).

[0082] As used herein, the term "propylene-based polymer" means a polymer a majority amount (by weight) of polymerized propylene monomer, and optionally at least one The term refers to a polymer that may contain one or more comonomers.

[0083] As used herein, the term "composition" refers to the materials that make up the composition. This includes mixtures, as well as reaction and decomposition products formed from the materials of the composition. .

[0084] When the term "blend" or "polymer blend" is used, it refers to two or more A blend refers to a mixture of the above polymers. A blend may or may not be miscible. In some cases, the blend is phase separated (not phase separated at the molecular level). In some cases, the phase separation may not be present. A blend may contain one or more domain configurations. It may or may not include the option. Determined by electron spectroscopy, light scattering, X-ray scattering, and other methods known in the art. A blend is a combination of two or more polymers at a macro level (e.g., melt blended resin). or compounding) or at the micro level (e.g. in the same reactor This can be achieved by physically mixing the components in a simultaneous molding process.

[0085] As used herein, the term "reactor system" refers to a reactor in which a polymer is polymerized and synthesized. This refers to a component (device) that is used for the purpose of isolating Components / devices include, but are not limited to, one or more reactors, These include a secondary compressor, a primary compressor, and a booster compressor. As used herein, the term "reactor configuration" refers to a poly One or more reactors (e.g., autoclaves) used for the purpose of polymerizing the polymer. and / or tubular reactor), and optionally one or more reactor preheaters. The reactor may be jacketed.

[0086] As used herein, the term "reaction zone" refers to the area in which the free radicals are added. and / or by breaking down the ingredients into free radicals, and / or Decomposition of components initiates or re-initiates polymerization reactions, generating free radicals. The reactor zone.

[0087] As used herein, the term "polymerization temperature in the reaction zone" or similar terms The phrase refers to the maximum temperature measured within the reaction zone. Autoclave reaction zones are typically The temperature in the tubular reaction zone is usually listed as the peak temperature, whereas the temperature in the large zone is usually listed as the and marked.

[0088] "Comprising," "including," "having" The term "having" and its derivatives are specifically disclosed herein. If there are additional components, steps, or procedures, whether or not For the avoidance of doubt, the words "including All compositions claimed by using the term "comprising" are Any polymer or non-polymer, regardless of what may be stated otherwise. In contrast, "essentially" may include additional additives, adjuvants, or compounds. The term "becomes" is intended to include, within the scope of the following citation, any other The term "consists of" excludes any component, step, or procedure. does not exclude any component, step or procedure not specifically listed. This is what we have in mind.

[0089] Test Method density The samples for density measurement were prepared according to ASTM D 4703-10. It was pressed at 74°F (190°C) for 5 minutes at 10,000 psi (68 MPa). The temperature was kept at 374 for the five minutes mentioned. o F (190°C), then pressure was applied for 3 minutes. The pressure was then raised to 70°F (21°C) and 30°C (100°F). ,000 psi (207 MPa) and held for 1 minute. ASTM D792-08, Method B Measurements were performed within one hour of pressing the samples.

[0090] Melt Index Melt index (i.e. I2) is in accordance with ASTM D 1238-10 Measured by method B at 190°C / 2.16 kg, eluted every 10 minutes Reported in grams.

[0091] Nuclear magnetic resonance ( 13 C NMR) Approximately "3 g" for "0.25 to 0.40 g" of polymer sample in a 10 mm diameter NMR tube "Tetrachloroethane-d2 / orthodichloroethane containing 0.025M Cr(AcAc)3" The samples were prepared by adding a 50 / 50 mixture of benzene and toluene to the open tube. The samples were deoxygenated by placing them in a nitrogen environment for at least 45 minutes. Using a heat block and heat gun, heat the tube and its contents to 150°C. The samples were dissolved and homogenized by centrifugation. Each dissolved sample was visually inspected for homogeneity. The samples were thoroughly mixed immediately prior to analysis, but were not cooled, and the heated NMR samples were Inserted into the holder.

[0092] All data were collected using a Bruker 400 MHz spectrometer. The pulse repetition delay was set to 6 seconds, the flip angle was set to 90 degrees, and the reverse Data were acquired at a sample temperature of 120°C using gated decoupling. The measurements were also performed in locked mode on non-rotating samples. Prior to acquisition, the samples were allowed to thermally equilibrate for 7 minutes. 13 The C NMR chemical shift is 30.0pp The "C6+" value is an internal reference to the EEE triad of m in LDPE. This is a direct measurement of C6+ branching and does not distinguish long branches from "chain ends." The "2 ppm" peak is the third carbon from the end of every chain or branch with 6 or more carbons. and is used for the purpose of calculating the "C6+" value. The CO units per 1000 C are: Calculated as the peak integral at 43 ppm divided by 2. Ethylene / CO Copolymer In this case, the mole percentage (mol%) value of CO and the weight percentage (wt%) value of CO are the same. The mole percentage (Mol%) of CO is calculated as follows: CO units / 1000C = moles of CO per 1000 total carbon atoms; Molar ethylene = (1000-CO units / 1000C) / 2.

[0093] Nuclear magnetic resonance ( 1 H NMR) Sample preparation Approximately 130 mg of sample was placed in a NORELL 1001-7, 10 mm NMR tube. 3.25g 50 / 50 weight, tetrachloride containing 0.001M Cr(AcAc)3 The sample was prepared by adding the antioxidant "perchloroethane-d2 / perchloroethylene". To prevent this, N2 was bubbled into the solvent via a pipette inserted into the tube. The samples were purged for approximately 5 minutes. Each tube was capped and sealed with TEFLON tape. The samples were soaked overnight at room temperature to promote dissolution. The samples were exposed to O2 during storage, before and after preparation. The samples were stored in an N2-purged box to minimize exposure to chlorine. To do this, the samples were heated to 115°C and vortexed.

[0094] Data Acquisition Parameters Bruker Dual DUL High Temperature CryoProbe equipped Bruk er AVANCE 400MHz spectrometer, sample temperature 120℃, 1 Conduct H NMR Two experiments were carried out to obtain the spectrum. This is a control spectrum for quantifying the entire ton. Note that a double pre-saturation experiment was performed to The high sensitivity spectrum allows quantification of end groups, while suppressing the polymer backbone peaks. The control was ZG pulse, 4 scans, SWH 10,000Hz, AQ 1.6 The double presaturation experiment was performed with a modified pulse sequence, T D 32768, 100 scans, DS 4, SWH 10,000Hz, AQ 1.6 It was executed at 4 seconds, D1 at 1 second, and D13 at 13 seconds.

[0095] Data Analysis − 1 H NMR calculation Residues of TCE (tetrachloroethane)-d2 (at 6.0 ppm) 1 The signal from H is integrated. The integrals from 3 ppm to 0.5 ppm were calculated from the polymer concentration in the control experiment. In the presaturation experiment, the TCE signal was also set to 100. , the corresponding integrals of unsaturation (vinylene at about 5.40-5.60 ppm, 5 ppm tri-substituted, about 4.95-5.15 ppm vinyl, and about 4.70-4.90 ppm pm vinylidene) was obtained.

[0096] Presaturated experimental spectra show cis- and trans-vinylene, trisubstituted, vinyl, and The area of ​​vinylidene was integrated. The integral for the whole polymer from the control experiment was divided by 2 to obtain the carbon We get a value that represents x thousand pieces (i.e., if the polymer integral = 28,000, this is 14,0 00 carbon, where X=14).

[0097] Dividing the unsaturated group integral by the corresponding number of protons contributing to that integral gives represents the number of moles of each type of unsaturation per thousand carbons X. Divide the moles of each type of unsaturation by X. This gives the moles of unsaturated groups per 1000 moles of carbon.

[0098] Melt Strength Melt strength measurements were performed using a Gottfert Rheotester 2000 capillary. - Gottfert Rheotens 71.97 (Go The melted samples ( Approximately 25-30 grams) with a Goettfert Rheotester 2000 capillary The capillary rheometer was fitted with a 30 mm long, 10 mm diameter 2.0 mm, aspect ratio (length / diameter) 15, flat entrance angle (180 degrees) The sample was equilibrated at 190°C for 10 min, and then moved at a constant piston speed of 0.26 The piston was moved at 5 mm / sec. The standard test temperature was 190°C. The specimen was placed under the die. Acceleration of 2.4 mm / s on one axis for a pair of acceleration nips located at 100 mm from the center 2 Pull The tension was recorded as a function of the take-up speed of the nip rolls. The melt strength was The plateau force (cN) before the strand broke was reported. The conditions used were: plunger speed = 0.265 mm / sec; wheel acceleration degree=2.4mm / s 2 ;capillary diameter = 2.0 mm;capillary length = 30 mm; and barrel diameter = 12mm.

[0099] Dynamic mechanical spectroscopy (DMS) The resin was then cooled to 350°F for 5 minutes under 1500 psi pressure in air. The samples were then compression molded into "inch" circular plaques. The samples were then removed from the press and placed on a countertop. The mixture was placed on a rack and allowed to cool.

[0100] Constant temperature frequency sweeps were performed using a Texas Instruments Induction Advanced Rheome A tric Expansion System (ARES) was used to perform the experiment under nitrogen purging. The sample was placed on the plate and melted at 190°C for 5 minutes. The plate was closed to a gap of 2 mm and the sample was trimmed (outside the 25 mm diameter plate). The excess specimen extending beyond the circumference was removed) and the test was started. A delay of 0.1–1 min was included to allow for temperature equilibration. The test was carried out at 190°C with a frequency range of 100 rad / s. The strain amplitude was constant at 10%. From these data, the complex viscosity η * , tangent δ (i.e. loss tangent), 0 Viscosity at .1 rad / sec (V0.1), viscosity at 100 rad / sec (V100), and viscosity at .1 rad / sec (V100) The intensity ratio (V0.1 / V100) was calculated.

[0101] Triple Detector Gel Permeation Chromatography (TDGPC), i.e. conventional GPC , Light Scattering GPC, Viscosity Measurement GPC and gpcBR The GPC techniques used herein (conventional GPC, light scattering GPC, and GPC BR) includes triple detector gel permeation chromatography (3D-GPC or TDGP The Waters (Massachusetts) 1000-μL ... Milford, Massachusetts Model 150C High Temperatur Other suitable high temperature GPC instruments include The models used are the Model 210 and Model 220 manufactured by Polymer Laboratories (Shropshire, UK). Model 220), Precision Detector Two-angle laser light scattering (LS) detection from Electron Microscopy (Amherst, Massachusetts) Model 2040, Polymer ChAR (Valencia, Spain) R4 infrared detector, Viscotek (Houston, TX) The test piece was equipped with a 150R 4-capillary solution viscometer (DP) manufactured by Epson.

[0102] A GP equipped with these latter two independent detectors and at least one of the former detectors C is sometimes called "3D-GPC" or "TDGPC", but is not known as "GPC". The term generally refers to conventional GPC. Data collection was performed using a Viscotek TriSE Viscotek Data Man C software, version 3, and 4 channels The study was carried out using a Polymer Laboratory DM400. The system was also equipped with an on-line solvent degasser manufactured by Eppendorf Chemical Industries, Ltd. (Shropshire, UK).

[0103] The eluent from the GPC column set was passed through the LS detector, the IR4 detector, and then the DP detector. The beam was passed through each of the serially arranged detectors in the order of the detectors. A systematic approach to this is presented by Balke, Mourey, et al. y and Balke,Chromatography Polym.,Chapte r 12,(1992))(Balke,Thitiratsakul,Lew,Che ung,Mourey,Chromatography Polym.,Chapter 13, (1992)) and triple checking was performed. Optimization of the detector logs (MW and intrinsic viscosity) is described in the Light Scattering (LS) GPC section below. As outlined in the paragraph following Eq. (5), results using a wide range of polyethylene standards and This is obtained.

[0104] Any suitable high temperature GPC column can be used, for example a 30 cm long Shodex HT8 03 13 micron columns x 4, 20 micron mixed pore size packing 30cm P Polymer Labs columns × 4 (MixA LS, Polymer Laboratories, Inc.) or 13 micron mixed-pore-size pack ing) 30 cm Olexis-LS columns × 4 (Polymer Laboratory Co., Ltd.) The column used here is an Olexis-LS column. Sample Carousel Compartment The chromatograph was operated at 140°C and the column compartment at 150°C. The concentration was 0.1 g polymer in 50 ml solvent. The solvent for the sample preparation was 2,6-di-tert-butyl-4-methylphenol. The suspected hazardous substance was 1,2,4-trichlorobenzene (TCB) containing 200 ppm of BHT. The solvent was sparged with nitrogen. The polymer sample was gently stirred at 160° C. for 4 hours. Injection volume was 200 microliters. The flow rate through the GPC was set at 1 ml / min.

[0105] Conventional GPC Conventional GPC uses an IR4 detector to analyze 21 narrow molecular weight distribution polystyrenes. The GPC column set was calibrated by running standards. The molecular weight (MW) of the standards was: The standard is six "cocktails" ranging from 580g / mol to 8,400,000g / mol. Each standard mixture had at least one decade between the individual molecular weights. The standard mixture was prepared by Polymer Lab Polystyrene standards were purchased from Biotech (Branch Press, NY). If the molecular weight is 1,000,000 or more, it is 0.025 g in 50 mL of solvent. If the concentration was less than 0.00 g / mol, the solution was prepared as 0.05 g in 50 mL of solvent. The toluene was dissolved at 80°C with gentle stirring for 30 minutes. In this study, the narrow standards mixture was run first, with the highest molecular weight components analyzed first. When the polyethylene standard peak molecular weight was converted to the polyethylene molecular weight, the formula (1) (Williams and Ward,J.Polym.Sci.,Polym.Letters,6,6 21 (1968) was used.

number

number

[0106]

number

[0107]

number

[0108] Light scattering (LS) GPC For LS GPC, the Precision Detector PDI2040 detector A Model 2040 was used. Depending on the sample, the light scattering detector was set at an angle of 15° or 90° were used in the calculations. The angle used here was 15°.

[0109] Molecular weight data was obtained from Zimm (Zimm, BH, J. Chem. Phys., 16 , 1099 (1948)), and Kratochvil (Kratochvil, P., Classical Light Scattering from Polymer Solutions, Elsevier, Oxford, NY (1987) The overall notes used to calculate the molecular weight were obtained by a method consistent with that described in The input concentration is determined by the area of ​​the mass detector and the mass detector constant (preferably linear polyethylene homopoly (or weight average molecular weight derived from one of the polyethylene standards with known molecular weights) To obtain the calculated molecular weight, the molecular weight is derived from one or more polyethylene standards as described below. The light scattering constant was calculated using the refractive index concentration coefficient (dn / dc) = 0.104. The response of the mass detector and the light scattering constant are linear for molecular weights above about 50,000 g / mole. The viscosity should be calculated from the standard. The viscometer should be calibrated using the method described by the manufacturer or Standard Reference Material (SRM) 1475a (available from the National Institute of Standards and Technology (NIST)) This can be achieved using published values ​​of suitable linear standards. Secondary viral count effect (vs. molecular weight) The chromatographic concentration is sufficiently high to eliminate the effect of concentration on the is assumed to be low.

[0110] In 3D-GPC, the following steps are used to calculate the absolute weight average molecular weight ("Mw, Abs"). Equation (5) is used, and the "peak area" method is used to improve accuracy and precision. The "Light Scattering Detection Area (LS Area)" and "Concentration Detection Area (Conc. Area)" are It is produced by a combined chromatography / detector system.

[0111]

number

[0112] For each LS profile, the x-axis (log MWcc-GPC) (cc is the conventional calibration curve) The chromatographic parameters (referred to as "chromatographic parameters") are determined as follows: First, using polystyrene standards (see above), The retention volume is expressed as log MW PS Then, the formula 1 (M polyethylene = A x (M Polystyrene) B ) to find "log MW PS " to "log MW PE " Convert log MW PE ” Scale corresponds to the x-axis of the LS profile in the experimental section. It functions as (log MW PEis equivalent to log MW(cc-GPC). The y-axis of the S profile is the response of the LS detector normalized to the mass of the injected sample. First, the traditional calibrations for both molecular weight and intrinsic viscosity (in "cc") are used as a function of elution volume. The molecular weight and solid state of a linear polyethylene standard such as SRM1475a or equivalent was Calculate the viscosity.

[0113] In the low molecular weight region of the GPC elution curve, the presence of antioxidants or other additives may There are significant peaks that are known to be present, which allow the number average distribution of the polymer sample. The molecular weight (Mn) is underestimated and is defined as Mw / Mn (Mw is the weight average molecular weight). Therefore, by excluding this extra peak, From the GPC elution, the true molecular weight distribution of the polymer sample can be calculated. This process is The peak skim function of the data processing procedure in chromatographic analysis is described as This process removes the additive peak from the GPC elution curve. After the analysis, the molecular weight of the sample is calculated from the GPC elution curve.

[0114] Differential Scanning Calorimetry (DSC) Melting and crystallization of polymers over a wide range of temperatures using Differential Scanning Calorimetry (DSC) For example, the RCS (refrigeration cooling system) and the autosampler were equipped The analysis was carried out using a TA Instruments Q1000 DSC. A nitrogen purge gas flow of 50 ml / min was used during testing. Each sample was melt pressed at approximately 175°C. After forming the melted sample into a thin film, the melted sample was air-cooled to room temperature (approximately 25°C). The material was a 0.1-0.2 gram sample pressed at 175°C, 1500 psi, and 30 seconds. The film was formed by forming a film having a thickness of 0.1 to 0.2 mils. A 0.0 mg, 6 mm diameter specimen was extracted from the cooled polymer, weighed, and packed into a lightweight aluminum The plates were then placed in a dish (approximately 50 mg) and crimped shut. Analysis was then performed to determine their thermal properties. carried out.

[0115] The thermal behavior of the sample is monitored by ramping the sample temperature up and down to generate a heat flow vs. temperature profile. First, the sample was rapidly heated to 180°C and kept isothermal for 5 minutes. The thermal history was then removed. The sample was then cooled to -40°C at a cooling rate of 10°C / min, and then cooled to -40°C. The sample was then isothermally held at 150°C for 5 min. The sample was then heated to 150°C at a heating rate of 10°C / min ( (This is the "second heat" ramp). The cooling and second heating curves were recorded. The cooling curves were Analyze by setting the baseline endpoint at -20 °C from the start of crystallization. The thermal curve was set with the baseline endpoint ranging from -20°C to the end of melting. The values ​​determined were the peak melting temperatures (T m ), peak crystallization temperature degree(T c ), heat of fusion (H f ) (Joules per gram). The calculated The crystallinity percentage obtained is the crystallinity percentage = ((H f ) / (292J / g))×100 It was determined.

[0116] Heat of fusion (H f ) and peak melting temperatures were reported from the second heat curve. The curing temperature is calculated from the cooling curve.

[0117] Calculation of the 1-hour half-life of the initiator The 1-hour half-life of an initiator is determined by differential scanning calorimetry of a dilute solution of the initiator in monochlorobenzene. Measurement - Calculated by thermal activity monitoring (DSC-TAM). The decomposition kinetics of hydroperoxides in water are calculated by titration. Niuss' formula: k d =Ae -Ea / RT and t 1 / 2 =ln(2) / k d ,(where k d teeth , s -1 is the rate constant of initiator dissociation at s -1 is the Arrhenius frequency coefficient of where Ea is the activation energy for initiator dissociation in J / mole s and R is 8.314 2 J / mol K, T is temperature in K (Kelvin), and t 1 / 2 is half a second The decay time (s) can be calculated. High-temperature free radical initiators are those that react at temperatures between 130°C and 200°C. Defined as an initiator that has a "one hour half-life" at temperatures in the range. Mid-Temperature Free Radical Initiator is defined as an initiator that has a "one hour half-life" at temperatures ranging from 90°C to 129°C. Low temperature free radical initiators have a "one hour half-life" at temperatures ranging from 30°C to 89°C. It is defined as an initiator.

[0118] experiment Preparation of the Inventive Ethylene-Based Polymers Examples 1 to 15 of the present invention The inventive examples were produced in the same process reaction system. Therefore, the results may vary from one experiment to another. Where the same equipment is referred to during Figure 1 shows a block diagram of the process reaction system used to produce the above examples. This is a block diagram.

[0119] The process reactor system in Figure 1 is a partially closed loop dual recycle high pressure, low density This is a polyethylene production system. The process reaction system consists of a fresh ethylene supply line 1; a booster - Primary Compressor "BP", Hyper Compressor "Hyper (Hyp The reactor is composed of a two-zone autoclave and a two-zone tube reactor. The autoclave / tube reactor was configured as follows: first reaction zone 1; 1 peroxide initiator line 2; second reaction zone 2; second peroxide initiator line third reaction zone 3; third peroxide initiator line 4; fourth tube reaction zone 4; 4th peroxide initiator line 5; mounted around the outer shell of the tube reactor section Cooling jacket (using high pressure water); High pressure separator "HPS"; High pressure recycling Recycle line 6; Low pressure separator "LPS"; Low pressure recycle line 7; CTA supply line 8; and carbon monoxide supply line 9.

[0120] The reactor has four reaction zones, defined by the location of the peroxide injection points. The feed port of the first reaction zone is attached to the autoclave section. The autoclave section receives 50% of the total reactor feed. First reaction zone The second reaction begins at peroxide injection point #1 and ends at peroxide injection point #2. The zone begins at peroxide injection point #2, which contains the entire supply The remaining 50% of the product is injected into the second reaction zone, which ends at peroxide injection point #3. The third reaction zone is at peroxide injection point #3 near the beginning of the tube reactor. The fourth reaction zone begins at peroxide injection point #1 and ends at peroxide injection point #4. It starts at #4 and ends just before the reactor pressure control valve.

[0121] In the present invention, t-butyl peroxy-2-ethylhexanoate (TBPO), te rt-Butyl peroxypivalate (PIV) and isoparaffinic hydrocarbon solvents (boiling The mixture containing the initiator mixture for the first and second injection points was used as the initiator mixture for the first and second injection points. At injection points #3 and #4, di-t-butyl peroxide (DTBP), TPO Mixtures containing ethylene glycol and isoparaffinic hydrocarbon solvents were used. Table 1 shows the composition of each mix. The composition is shown.

[0122] In the present invention, propylene and methyl ethyl ketone were used as chain transfer agents (CTA). The CTA mix was used in combination with the booster / primary compressor suction side. The composition of the CTA feedstock for this process was determined by the process run. The melt index of the product was adjusted by adjusting it to correspond to:

[0123] Carbon monoxide was used as a comonomer. Carbon monoxide was used as an intake booster / primary The ethylene stream was injected by a compressor. Table 2 shows the reactor process used for production. The conditions for the reaction are shown in Fig. 1. Carbon monoxide has an inhibitory effect on the peroxide used. Therefore, a 3:1 weight ratio mix of PIV to TBPO was injected into injection points #1 and #2. The mixture was used as the transport mixture. By providing a section, TPO is prevented from being carried over into the reactor tube. In addition, by avoiding a target with a temperature of over 240°C, This reduces the need to use DTBP, which has a high dissociation temperature and therefore inhibits CO. This can lead to carryover into the tubular reactor. These process conditions allow for the decomposition of ethylene during the use of CO. The risk is reduced. Table 2 shows the process conditions.

[0124] [Table 1]

[0125] [Table 2-1] [Table 2-2]

[0126] Comparative Example 1 In Comparative Example 1 (CE1), t-butyl peroxy-2-ethylhexanoate (TBP O), tert-butyl peroxypivalate (PIV), and isoparaffinic hydrocarbons A mixture containing a solvent (having a boiling point range of more than 179°C) is injected into the initiator at the first and second injection points. At injection points #3 and #4, di-t-butyl peroxide (DTBP) was used as a mixture. A mixture containing TPO and an isoparaffinic hydrocarbon solvent was used. The flow rates of the peroxide initiator and solvent solutions used are shown.

[0127] [Table 3-1] [Table 3-2]

[0128] In Comparative Example 1, propylene and methyl ethyl ketone were used as chain transfer agents (CTA). The CTA mix was used in combination with the booster / primary compressor suction side. Carbon monoxide was used as the comonomer for Comparative Example 1. Carbon dioxide was injected into the ethylene stream at the suction booster / primary compressor. 3 shows the reactor process conditions used in the preparation of Comparative Example 1.

[0129] Tables 5 to 11 show the properties of the examples and comparative examples. Comparative Example 2 (CE2) is a Dow Chemical Dow LDPE 5004I (4.15 melt index) available from Cal Company , 0.924 g / cc).

[0130] [Table 4]

[0131] Properties of the polymers of the present invention and comparative polymers (IE1 to IE15, CE1, CE2) Table 5 shows the melt index (I2), density, melt strength, and melt strength data. The melt indexes IE1 to IE15 are used for extrusion coating or casting. The range is suitable for use in strip film applications. The density of IE1 to IE15 is high (0.93 5 to 0.941 g / cc), due in part to the ingestion of carbon monoxide (CO). The unexpected increase in melt strength of these samples is due to the fact that This is especially true when samples are exposed to elevated CO levels, as shown in FIG. It is useful in applications such as extrusion coating, especially because it has a broad molecular weight distribution. This is because the cc-GPC Mw / Mn in Table 6 is an example. PC-related characteristics were derived using a combination of LS detector, viscosity detector, and concentration detector. The DMS viscosity data shown in Table 8 is summarized as follows: , Viscosity measured at 1 rad / s, 10 rad / s and 100 rad / s; Viscosity ratio 0.1 The ratio of the viscosity measured at rad / s to that measured at 100 rad / s (19 0°C); and loss tangent measured at 0.1 rad / s and 190°C.

[0132] Table 9 shows the CO (carbon monoxide) content and the number of branches per 1000 C ( 13 CN These polymers contain amyl or C5 branches. These amyl or C5 branches are substantially linear polyethylenes, e.g., A FFINITY polyolefin plastomer, or LLDPE, e.g. DOWLEX poly The manufacturer of both polyethylenes is Dow Chemical. IE1 to IE15 and Comparative Examples 1 and 2 are made by Cal Company. In other words, the examples of the present invention contain 0.5 amyl groups (branched) or more per unit time. The amyl group (branched) exceeds 1.0 per 1000 carbon atoms. The CO content level is 2-4 mol% CO or 2-4 wt% CO. , 1 The branching results of H NMR are shown.

[0133] Table 11 shows the melting points (T m ), heat of fusion, crystallinity (%), and crystallization point. As shown in FIG. 4, the melting point of the inventive example is relatively low because This is because of its high density.

[0134] [Table 5]

[0135] [Table 6]

[0136] [Table 7]

[0137] [Table 8]

[0138] [Table 9]

[0139] [Table 10]

[0140] [Table 11]

[0141] Extrusion Coating The present invention (IE) and comparative example (CE) shown in Table 12 are black Clawson extrusion coated. Black-Clawson Extrusion Coating L Line is 3.5 inches long and 3 inches in diameter. It is composed of a single flight screw with a ratio of 0:1 and a compression ratio of 4:1. Located near the end of the strait were two spiral Mattock mixing sections. Resin evaluation utilized an extrusion speed of 90 RPM, resulting in approximately 250 lbs / hr. The output was 50 lb / ream brown kraft at a line speed of 440 ft / min. Approximately 1 mil of coating was applied to the paper.

[0142] The specimens were cut to the dimensions of 24 inches by 36 inches. Two "X" strips were placed on each specimen. On each line, an "X-cut" of approximately 2 inches was made across the specimen. Each "X-cut" The "X-cut" was made approximately 6 inches from the edge of the polymer coating of each specimen. The penetration points were limited to the polymer coating. A utility knife was used to partially separate it from the paper. The operator removed the released po The polymer was held in one hand and the test piece was held in the other hand. The polymer was removed from the paper by about 1-2 inches. Slowly tow the vehicle until it was within reach. Slow towing took about 5 to 10 seconds. A "pass" value was recorded because the adhesion between the polymer layer and the surface of the paper was not as good as that of the paper itself. When the adhesion between the fibers is stronger than the matrix adhesion (i.e., when more than 5% of the paper surface is polymer A "fail" value was recorded when the paper fibers were almost completely removed. Little to no adhesion (or less than 5% of the paper surface is peeled off with the polymer) In this case, the polymer layer was pulled away from the paper surface. The percentage of the surface area is the percentage of the total area of ​​the polymer coating that was removed from the paper substrate. For each polymer, one specimen was examined, with two specimens. I made two "X cuts."

[0143] [Table 12]

[0144] Table 12 shows the results of fiber tear adhesion testing of kraft paper. In some cases, as evidenced by the inventive examples, it is "passed" at temperatures between 590°F and 620°F. In some cases, as evidenced by comparative example 2, it is "failed" at temperatures between 590°F and 610°F. Thus, the adhesion of the inventive examples is favorable compared to that of comparative example 2. Also, the inventive examples can be extrusion coated at high speeds and temperatures. The present application also relates to the following aspects: (1) A composition comprising an ethylene / CO interpolymer formed by high pressure free radical polymerization, said ethylene / CO interpolymer having the following characteristics: a) a CO content of "greater than 0" to 10 weight percent CO (carbon monoxide) based on the weight of the interpolymer; b) Melting point (T m ) (unit: °C) are related as follows: T m (℃) is 601.4 × (density, unit: g / cc) - 452.5 (℃) or less. (2) The composition according to (1), wherein the ethylene / CO interpolymer satisfies the following relationship: MS(cN)≧2.0(wt%CO)+2.0. (3) The composition according to (1) or (2), wherein the ethylene / CO interpolymer has a melt index (I2) of 0.1 to 100 g / 10 min. (4) The T of the ethylene / CO interpolymer m The composition according to any one of (1) to (3), wherein (°C) is 601.4 × (density, unit: g / cc) - 460.0 (°C) or more. (5) The melting temperature (T m ) is 105.5°C to 110.5°C. (6) The composition according to (1) or (2), wherein the ethylene / CO interpolymer has a density of 0.910 to 0.990 g / cc. (7) The ethylene / CO interpolymer has an amyl group level of 0.5 amyl groups per 1000 carbon atoms or more ( 13 The composition according to any one of (1) to (6), wherein the molecular weight is 1.0 or more, as calculated by C NMR. (8) The composition according to any one of the above (1) to (7), wherein the ethylene / CO interpolymer is an ethylene / CO copolymer. (9) The composition according to any one of (1) to (8) above, further comprising a second ethylene-based polymer. (10) The composition of claim 9, wherein the second ethylene-based polymer is selected from LDPE, ethylene / α-olefin copolymer, or a combination thereof. (11) An article comprising at least one component formed from the composition according to any one of (1) to (10) above. (12) The article according to (11) above, wherein the article is a coated substrate or film. (13) The article according to (11) or (12), wherein the article is a coating and is produced by extrusion coating or extrusion lamination. (14) A process for forming the composition according to any one of (1) to (10), comprising polymerizing ethylene and CO using a high pressure free radical polymerization process to form the ethylene / CO interpolymer, the reactor configuration in which the polymerization occurs comprising at least one autoclave reactor with two or more reaction zones and at least one tubular reactor with two or more reaction zones; and In the autoclave reactor, the polymerization is carried out by auto At least one "medium temperature free radical initiator" labeled FRl auto and in each reaction zone within said autoclave reactor, auto vs. FRL auto Weight ratio auto ) is 0.04 to 1.00, and In the tubular reactor, the polymerization is tube At least one "high temperature free radical initiator" labeled FRm tube and in each reaction zone of the tubular reactor, tube vs. FRm tube Weight ratio tube ) is 0.06 to 0.50, the process. (15) The process according to (14), wherein the polymerization temperature in each reaction zone of the autoclave reactor is independently 190°C to 270°C. (16) The process according to (14) or (15), wherein in the autoclave reactor, the weight ratio of "the amount of ethylene added to a reaction zone" to "the amount of CO added to the same reaction zone" is 388 to 39. (17) The process according to any one of (14) to (16), wherein the polymerization temperature of each reaction zone of the autoclave reactor is independently less than 250°C. (18) The process according to any one of (14) to (17), wherein the polymerization temperature of each reaction zone of the tubular reactor is independently 260°C to 300°C. (19) The process according to any one of (14) to (18), wherein the ethylene / CO interpolymer is an ethylene / CO copolymer.

Claims

1. A composition comprising an ethylene / CO interpolymer formed by high pressure free radical polymerization, said ethylene / CO interpolymer having the following properties: a) a CO content of "greater than 0" weight percent to 10 weight percent CO (carbon monoxide) based on the weight of the interpolymer; b) The melting point (Tm) (unit: °C) has the following relationship: Tm (°C) is 601.4 x (density, unit: g / cc) - 452.5 (°C) or less, The ethylene / CO interpolymer has a Tm (°C) of 601.4 x (density, g / cc) - 460.0 (°C) or greater; The melting temperature (Tm) of the ethylene / CO interpolymer is from 106.9° C. to 108.2° C., and the density of the ethylene / CO interpolymer is from 0.935 to 0.9407 g / cc. composition.

2. 2. The composition of claim 1, wherein the ethylene / CO interpolymer satisfies the following relationship: MS(cN)≧2.0(wt% CO)+2.

0.

3. The melt index (I 2 3. The composition according to claim 1, wherein the viscosity of the polymer is 0.1 to 100 g / 10 min.

4. The ethylene / CO interpolymer has an amyl group level of 0.5 amyl groups per 1000 carbon atoms or more ( 13 2. The composition of claim 1, wherein the molecular weight is 1.0 or less, as calculated by C NMR.

5. The composition of claim 1 , wherein the ethylene / CO interpolymer is an ethylene / CO copolymer.

6. 10. The composition of claim 1, wherein the composition further comprises a second ethylene-based polymer, the second ethylene-based polymer selected from an LDPE, an ethylene / α-olefin copolymer, or a combination thereof.

7. 13. An article comprising at least one component formed from the composition of claim 1, said article being a coated substrate or film, said coating being produced by extrusion coating or extrusion lamination.

Citation Information

Patent Citations

  • High frequency heating can be plastics

    JP1985501218A

  • Ethylene-based polymer and its manufacturing process

    JP2016508175A

  • An ethylene polymer containing units derived from carbon monoxide and a rheology modifier

    JP2017519877A

  • Process for preparing ethylene-based polymers using carbon monoxide partitioning

    JP2017523273A

  • Compositions comprising ethylene-carbon monoxide copolymers

    WO2017189299A1